2007
DOI: 10.1002/cne.21389
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical characterization of insulin receptor‐expressing primary sensory neurons in wild‐type and vanilloid type 1 transient receptor potential receptor knockout mice

Abstract: The insulin receptor (IR) is expressed by a subpopulation of primary sensory neurons (PSN), including a proportion of cells expressing the nociceptive transducer vanilloid type 1 transient receptor potential receptor (TRPV1). Recent data suggest functional links between the IR and other receptors, including TRPV1, which could be involved in the development of PSN malfunctions in pathological insulin secretion. Here we used combined immunohistochemical labelling on sections from L4-5 dorsal root ganglia of wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 78 publications
10
41
0
Order By: Relevance
“…Insulin itself also acts as a trophic factor in neural crest development [13] after injury [14], and a subtype of sensory neurons expresses the insulin receptor [15]. Islet-mediated stimulation of NCSC differentiation in the cocultures may in turn promote NCSC production of additional growth-supporting factors, for example, TNF-a, IL-1, nerve growth factor, and leukemia inhibitory factor, which can be produced by peripheral glia or neurons [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin itself also acts as a trophic factor in neural crest development [13] after injury [14], and a subtype of sensory neurons expresses the insulin receptor [15]. Islet-mediated stimulation of NCSC differentiation in the cocultures may in turn promote NCSC production of additional growth-supporting factors, for example, TNF-a, IL-1, nerve growth factor, and leukemia inhibitory factor, which can be produced by peripheral glia or neurons [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in a different study, BCTC was proposed to keep mice lean by inhibiting TRPV4 channels . TRPV1-positive sensory neurons possess high-affinity insulin receptors (Baiou et al, 2007). Insulin was suggested to facilitate the redistribution of TRPV1 from intracellular organelles to the plasma membrane and thereby sensitize the neurons to TRPV1 agonists (see Bishnoi and Premkumar, 2013).…”
Section: E Transient Receptor Potential Channels In Obesity and Metamentioning
confidence: 99%
“…indicated that approximately 40% of DRG neurons express the insulin receptor and that approximately 75% of insulin receptor expressing neurons were co-labeled with peripherin (Baiou et al, 2007). TRPV1 co-labeling indicated 25% of all DRG neurons coexpress TRPV1 and the insulin receptor and that approximately 68% of TRPV1 positive neurons express the insulin receptor (Baiou et al, 2007). Furthermore, insulin receptor expression was not confined to one c-fiber subtype, as insulin receptor expressing neurons were co-labeled with either CGRP (peptidergic) or IB4 (non-peptidergic).…”
Section: Insulin As a Neurotrophic Factor In The Pnsmentioning
confidence: 99%